2016
DOI: 10.1371/journal.pone.0166184
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Water and Ion Channels in Diffuse Alveolar Damage Is Not Dependent on DAD Etiology

Abstract: IntroductionAquaporins and ion channels are membrane proteins that facilitate the rapid movement of water and solutes across biological membranes. Experimental and in vitro studies reported that the function of these channels and pulmonary edema resolution are impaired in acute lung injury (ALI). Although current evidence indicates that alveolar fluid clearance is impaired in patients with ALI/diffuse alveolar damage (DAD), few human studies have addressed the alterations in pulmonary channels in this clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
(62 reference statements)
0
15
1
3
Order By: Relevance
“…2 c). In 2016 in a small group of septic patients suffering from diffuse alveolar damage is was demonstrated that they have increased expression of AQP3 and AQP5 in the alveolar septum compared to healthy controls [ 62 ]. Recently it was demonstrated that Aqp5 expression is decreased after sepsis induction with cecal ligation puncture (CLP) in the lung of rats [ 63 , 64 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 c). In 2016 in a small group of septic patients suffering from diffuse alveolar damage is was demonstrated that they have increased expression of AQP3 and AQP5 in the alveolar septum compared to healthy controls [ 62 ]. Recently it was demonstrated that Aqp5 expression is decreased after sepsis induction with cecal ligation puncture (CLP) in the lung of rats [ 63 , 64 ].…”
Section: Introductionmentioning
confidence: 99%
“…AQP3 is expressed most strongly in the kidney collecting duct, the gastrointestinal tract, large airways (in basal epithelial cells and the nasopharynx), skin, and the urinary bladder; while AQP7 is expressed primarily in the testis, fat cells and, to a lesser extent in a subsegment of the kidney proximal tubule [36]. In addition, AQP3 is upregulated in the lung tissues during viral or bacterial-induced diffuse alveolar damage [37]. Based on this, the evidence that SARS-CoV-2 viral proteins interacts with host proteins with the highest expression in lung tissues [38], and the functional evidence of the fine mapped variants in the GWAS being eQTLs in lung tissues, our data supports AQP3 as the most likely gene of the 9p13.3 locus driving the association with COVID-19 hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…In this hypothesis, the alveolar surface liquid is maintained at an appropriate level through liquid secretion and absorption. Aquaporins, a type of specialized protein in the alveolar epithelium, and ion channels transfer the water from the alveolar airspace to the capillaries as needed to maintain this homeostasis (Pires-Neto et al, 2016;Wittekindt & Dietl, 2019). Using animal models and human lung autopsies, scientists are developing models that address aspects of fluid absorption (Matute-Bello et al, 2008).…”
Section: Patient (Host) Defense Mechanismsmentioning
confidence: 99%